STUDI TENTANG PENGARUH SELF CONCEPT, AGRESI, SERTA FUNGSI REGULASI DAN KONTROL, TERHADAP PERILAKU KRIMINAL (SUATU MODEL STUDI TENTANG PERILAKU KRIMINAL PADA NARAPIDANA DI LEMBAGA PERMASYARAKATAN KELAS 1 SUKAMISKIN BANDUNG). - Umar Yusuf (SCHEMA (Journal of Psychological Research), 2009)
The objective of this study is to obtain descriptions concerning (1) the influence of self –concept, aggression, and the function of regulation and control on criminal behaviour; (2) the process dynamics of variables as a model of criminal behaviour manifestation. The theory of self-concept from Markus (1977, 1986, 1990) is used to analyse the data.As described in many research done by psychologists, criminals have negative self-concept, low self esteem, low competencies, and low self-confidence. They are also very aggressive and impulsive. However, those research result did not show description of the dynamic relationship between factors that draw out criminal behaviours.To be able to describe the dynamic relationship between factors that draw out criminal behaviours; the comparative causality research design is employed using expost-facto data. Data was gathered from 82 prisoners at the Suka miskin penitentiary, and 58 university students as control group, using questionnaire to measure self concept that based on theory from Markus (1977). A self-report was administered to measure aggression that is based on theory from Loeber and Schmaling (1985). Another self-report was carried out to measure the function of self regulation and control that is based on Markus and Wurf (1987) theory. To measure the criminal behaviour, a self report was made based on the definition of criminal behaviour from Andrew and Bonta (1993).The result of this study shows that self-concept, aggression, and the function of regulation and control, contributed as much as 53.72% to the manifestation of criminal behaviour. The result also shows that the process of manifestation of a criminal behaviour starts from bad self-concept that is marked by aggressive reactions to any emotional stimulus that is perceived as a threat to their self-identity. This kind of perception distortion, along with the cognitive failure to deal with the perceived threat from the environment, lead to uncontrolled behaviour.